Pro ASP.NET 3.5 Server Controls and AJAX Components - Cameron, Rob (Apress, 2012)
With the explosion of the Internet, web development tools evolved as a combination of HTML and a scripting language, such as ASP or Perl, to generate dynamic output. With the advent of Microsoft’s .NET Framework, ASP.NET turned web development on its head by combining a design-time interface similar to Visual Basic with an HTML and JavaScript output that requires nothing more than a web browser for rending. With ASP.NET 3.5, HTML and JavaScript are combined in powerful ways via ASP.NET AJAX technology that helps connect client-side and server-side connection without losing point-and-click design-time support. We wrote this book to document the major improvements since ASP.NET 1.1, while also covering the fundamentals for those new to custom server control development. At the core of ASP.NET is server control technology. From the Page class to the Label control to web parts, all objects in ASP.NET are server controls. Server controls combine server-side execution in a well defined life cycle with browser-friendly rendering that includes down-level browsers as well as a plethora of mobile clients. Regardless of the target output, all server controls behave in a similar manner. Understanding this technology and how to leverage it in your own development efforts are the subjects of this book.